2021
DOI: 10.1007/s10530-021-02607-3
|View full text |Cite
|
Sign up to set email alerts
|

The dilemma of Guinea grass (Megathyrsus maximus): a valued pasture grass and a highly invasive species

Abstract: HAL is a multi-disciplinary open access archive for the deposit and dissemination of scientific research documents, whether they are published or not. The documents may come from teaching and research institutions in France or abroad, or from public or private research centers. L'archive ouverte pluridisciplinaire HAL, est destinée au dépôt et à la diffusion de documents scientifiques de niveau recherche, publiés ou non, émanant des établissements d'enseignement et de recherche français ou étrangers, des labor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 96 publications
0
25
0
Order By: Relevance
“…The invasive success of trade‐off species where the same characteristics that favour their intentional planting (i.e. vigorous growth, ability to persist and establish in a range of conditions) contribute to their invasive success has been recognized (Overholt & Franck, 2017; Rhodes et al, 2021; Scasta et al, 2015; Williams & Baruch, 2000). Our results identified that seed characteristics associated with increased propagule pressure is most important in determining levels of invasion in native communities.…”
Section: Discussionmentioning
confidence: 99%
“…The invasive success of trade‐off species where the same characteristics that favour their intentional planting (i.e. vigorous growth, ability to persist and establish in a range of conditions) contribute to their invasive success has been recognized (Overholt & Franck, 2017; Rhodes et al, 2021; Scasta et al, 2015; Williams & Baruch, 2000). Our results identified that seed characteristics associated with increased propagule pressure is most important in determining levels of invasion in native communities.…”
Section: Discussionmentioning
confidence: 99%
“…Jacobs] is a large-statured tropical grass that has been planted around the world for use as livestock forage (Burton et al 1973). Native to intertropical and southeast Africa, it is now considered an invasive species in parts of Asia, North and South America, Australia, and many tropical islands (CABI 2021) due to its ability to shade and outcompete other species (Rhodes et al 2021). In subtropical southern Texas, it is implicated in the long-term declines of ground-dwelling granivorous birds such as quail and the facilitation of cattle fever tick [Rhipicephalus microplus (Canestrini)] invasion (Esteve-Gassent et al 2014;Mercadier et al 2009;Vacek et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Hybrids of these species are found in East Africa (Savidan and Pernès 1982), and perhaps elsewhere, and have made taxonomic identification difficult (Clayton and Renvoize 1982). Megathyrsus maximus has been assigned multiple scientific names over the years (see Rhodes et al 2021), and the taxonomic confusion has been compounded by introductions from multiple African sources and approximately 35 cultivars listed in the Tropical Forages website (Cook et al 2005). Both tall and short forms of M. maximus exist, with 28 and 7 cultivars listed for each, respectively.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations